Analisis Strategi SWOT Terhadap Peningkatan Daya Saing Pada Swalayan Bersama - Helen Pryadarsani Harefa (Jurnal Niaga & Bisnis (e-journal), 2015)
A business venture like the Joint Self requires SWOT analysis strategies to overcome the constraints of business, and can win the competition either similar business as Indomaret, Alfamart and new entrants in the businesses around it. Formulation of the problem in this research is to investigate the application of SWOT strategies to improving the competitiveness of Bersama’s Supermarket. The method used is descriptive qualitative research method. Data obtained from observation, interviews, and documentation. Analysis using SWOT analysis. Informants were 18 people. The results showed that the position of the company's strategy is to be implemented during the quadrant aggressive strategy. Bersama’s supermarkets take advantage of opportunities and the strengths and get aggressive strategy for growth and self development. Keywords: Analysis, Strategy, SWOT, Increased Competitiveness